Pay for Performance (PFP) as a Strategic Tool in Enhancing the Performance of Registered Life Insurance Agents in Malaysia : A Case Study of Malaysia - Sakrawathi, Muthuletchumi Lin (2014)
The role of Human Resource Management (HRM) in an organization plays an essential part in building a positive and competent workforce. Many organizations are striving to bring out the best from their employees through various HR practices and one of the current evolutions of HR practice is reward system. A good reward system is a key motivator to attract, retain and continuously motivates the employees at work. In the context of this research, the concept of Pay for Performance (PFP) was studied in the area of insurance industry in Malaysia. The PFP plans are widely used as a remuneration strategy to motivate the insurance agents in order to enhance their performance at work. Therefore given the above scenario, the main objective of this study was to examine the influence of PFP plans as a strategic tool in enhancing the performance of registered life insurance agents in Malaysia. A total of seven PFP plans have been identified based on relevant literature and models to measure its effectiveness in enhancing the performance of the life insurance agents. The study deploys quantitative research method i.e.; used of self-administrated questionnaire as a tool to collect data from the respective respondents. A total of 150 questionnaires were distributed to target sample and 100 questionnaires were received and used for the purpose of the analysis. Data was analyzed using the SPSS tool for both descriptive and inferential analysis. The findings of the research showed that overall PFP plans in the context of Malaysian insurance agents‟ played a vital role in influencing and enhancing their work performance. Some of the key factors analyzed were commissions, cash incentives, bonuses, incentive travel, award, career planning & development and retirement plan. Based on the findings, discussions and recommendations were presented as part of strategic analysis in order to further improve the implementation of PFP as a pro-active tool in motivating and improving employees‟ performance in general and in the perspective of insurance industry specifically.